North Sumatra Farmer Behavior in Determining Level of Consumption: Islamic Economic Philosophy - Budi Harianto; Iin Suwita (Journal of Management and Business Innovations, 2023)
Persons are creatures of Allah SWT who have advantages over other creatures, i.e., having reason and lust. If a person's wants and needs are met, he will feel comfortable, happy, and relieved. Behavior can be defined as the actions of humans who carry out theories. In North Sumatra, especially plantation farmers who are Muslim, consuming cannot be separated from their position of faith. Faith is an important measure because it shares a point of view that tends to influence human character and attitude. It dramatically affects the quantity and quality of consumption through material or spiritual satisfaction. Then it forms the attitude of consumption trends in the market. From the results researched, the authors found a way of consumption for plantation farmers by prioritizing Halal and cleanliness principles, simplicity, generosity, justice, and morality in life. Therefore, the author wants to explain the need for guidance to harmonize human behavior based on economic concepts in Islamic Economic Philosophy as a benchmark that will give birth to Islamic thought. If implemented, it will lead to the pattern of an attitude of plantation farmers in determining the level of consumption in North Sumatra, which is worth Islamic worship.Keywords: Consumption Behavior, Farmers, Islamic Economic Philosophy